A method for preparing lithium manganese iron phosphate material

Through a multi-step preparation method, including carbon coating and multiple sintering, the conductivity and structural stability of lithium manganese iron phosphate material are improved, and the problems of low conductivity and high production costs of existing materials are solved, which is suitable for large-scale industrial applications.

CN119735185APending Publication Date: 2025-04-01HENAN LONGBAI NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924209.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate (LMFP) cathode materials have low electronic conductivity and ionic conductivity, which limits their performance in large-scale industrial applications. The existing improvement methods have problems such as structural instability, high production costs and limited electrical conductivity improvement.

Method used

A multi-step preparation method is adopted, including a single grinding to obtain a solid solution of carbon-coated ferromanganese phosphate, a low temperature sintering to form a crystal nucleus, a secondary grinding to replenish lithium and adding a second carbon source, a high temperature sintering allows lithium to be embedded in the crystal lattice, and a carbon source sintering regulates the particle size.

Benefits of technology

It improves the crystal structure integrity, compaction density, electronic conductivity and ionic conductivity of the material, reduces production costs and process complexity, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211230390000101
    Figure BDA0005211230390000101
  • Figure BDA0005211230390000111
    Figure BDA0005211230390000111
Patent Text Reader

Abstract

The present invention relates to the technical field of positive electrode materials, and in particular to a method for preparing a lithium iron manganese phosphate material. The present invention provides a method for preparing a lithium iron manganese phosphate material, comprising the following steps: S1, first grinding an iron source, a phosphorus source, a manganese source and a first carbon source to obtain a carbon-coated iron manganese phosphate solid solution; S2, spray drying and first sintering the carbon-coated iron manganese phosphate solid solution in sequence to obtain a sintered material; S3, second grinding the sintered material, a lithium source and a second carbon source to obtain a grinded material; S4, spray drying, second sintering and crushing the grinded material in sequence to obtain the lithium iron manganese phosphate material. The method for preparing the lithium iron manganese phosphate material of the present invention improves the material's crystal structure integrity, compaction density, and electrochemical properties such as electronic conductivity and ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a method for preparing lithium manganese iron phosphate material. Background Art

[0002] Lithium-ion batteries are widely used in various electronic devices due to their high voltage, high specific energy, long life and good charge-discharge cycle performance. Among them, lithium manganese iron phosphate (LiMnPO4, LMFP for short) as a positive electrode material has become an ideal choice for lithium-ion battery positive electrode materials due to its high theoretical specific capacity, good thermal stability and environmental friendliness. However, LMFP has low electronic and ionic conductivity, which seriously limits its performance in large-scale industrial applications.

[0003] At present, the methods for improving the conductive properties of LMFP include: coating the surface of LMFP with a layer of conductive material, such as carbon, graphene, etc., to form a conductive network, thereby improving the electronic conductivity of LMFP; doping metal ions (such as magnesium, aluminum, etc.) into the lattice of LMFP to enhance its ionic conductivity; optimizing the synthesis process of LMFP, such as using a sol-gel method, a hydrothermal method, etc., to improve the particle size distribution and morphology of LMFP, thereby improving its electrochemical performance.

[0004] The above method improves the electrical conductivity of LMFP to a certain extent, but there are still some problems. First, the existing coating technology can usually only improve the electronic conductivity of LMFP, but the effect of improving the ionic conductivity is limited, and the coating of the carbon layer also affects the compaction density of lithium manganese iron phosphate. Although the doping of metal ions can improve the ionic conductivity of LMFP, excessive metal ion doping may cause the structure of LMFP to be unstable, thereby affecting its electrochemical performance. Although the existing synthesis process can improve the particle size distribution and morphology of LMFP, it often requires complex process flow and high production cost, which to a certain extent limits the large-scale industrial application of LMFP. Therefore, how to develop a preparation method that can not only improve the electrical conductivity of LMFP, but also maintain its structural stability, and has a simple process and low cost, is a problem that needs to be solved urgently.

[0005] In view of this, this invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a lithium manganese iron phosphate material, which improves the material's crystal structure integrity, compaction density, and electrochemical properties such as electronic conductivity and ionic conductivity.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The present invention provides a method for preparing a lithium iron manganese phosphate material, comprising the following steps:

[0009] S1, grinding the iron source, the phosphorus source, the manganese source and the first carbon source for the first time to obtain a carbon-coated manganese iron phosphate solid solution;

[0010] S2, spray drying and first sintering the carbon-coated ferromanganese phosphate solid solution in sequence to obtain a sintered material;

[0011] S3, performing a second grinding on the sintered material, the lithium source and the second carbon source to obtain a grinding material;

[0012] S4, spray drying, second sintering and crushing the ground material in sequence to obtain the lithium manganese iron phosphate material.

[0013] Further, step S1 includes at least one of the following features (1) to (4);

[0014] (1) The iron source includes one or more of ferric phosphate dihydrate, ferric phosphate, ferric chloride, ferric sulfate, ferric nitrate and ferrous sulfate heptahydrate;

[0015] (2) the phosphorus source comprises one or more of phosphoric acid, diammonium hydrogen phosphate, lithium monohydrogen phosphate, lithium dihydrogen phosphate and lithium phosphate;

[0016] (3) The manganese source includes one or more of manganese sulfate, manganese acetate, manganese oxalate, manganese phosphate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide;

[0017] (4) The first carbon source includes one or more of Super P, graphene, carbon nanotubes and acetylene black.

[0018] Furthermore, in step S1, in the carbon-coated ferromanganese phosphate solid solution, the molar ratio of Fe element, Mn element and P element is (0.4-0.6): (0.4-0.6):1.

[0019] Furthermore, in step S1, in the carbon-coated ferromanganese phosphate solid solution, the molar ratio of the C element to the P element is (0.01-0.3):1.

[0020] Furthermore, in step S1, the first grinding includes: grinding until the average particle size of the solid particles is 0.35-2 μm.

[0021] Furthermore, in step S2, the first sintering includes: heat preservation treatment at 300-600° C. for 2-7 hours.

[0022] Further, in step S3, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium chloride, lithium dihydrogen phosphate and lithium acetate;

[0023] And / or, the second carbon source includes one or more of glucose, sucrose, starch, polyethylene glycol, oxalic acid and citric acid.

[0024] Further, in step S3, the molar ratio of the Li element in the lithium source to the Fe element in the sintering material is 1:(0.4-0.6);

[0025] And / or, the molar ratio of the C element in the second carbon source to the Li element in the lithium source is (0.01-0.3):1.

[0026] Furthermore, in step S3, the second grinding includes: grinding until the average particle size of the solid particles is 0.35-0.45 μm.

[0027] Furthermore, in step S4, the second sintering includes: heat preservation treatment at 600-780° C. for 5-9 hours.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The preparation method of the lithium manganese iron phosphate material of the present invention obtains a carbon-coated ferromanganese phosphate solid solution by primary grinding to form a crystal nucleus, and the crystal nucleus grows under the coating of a first carbon source during low-temperature sintering. During secondary grinding, lithium is supplemented and a second carbon source is added, and during high-temperature sintering, lithium is embedded in the ferromanganese phosphate lattice, and the particles can be prevented from growing excessively under the coating of the carbon source; thereby, the crystal structure integrity of the material is improved, the particle size is effectively controlled, the ion transmission path is shortened, the compaction density of the material is improved, the electronic conductivity is improved, and the ion conductivity is enhanced. DETAILED DESCRIPTION

[0030] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0031] The following is a detailed description of a method for preparing a lithium manganese iron phosphate material of the present invention.

[0032] In some embodiments of the present invention, a method for preparing a lithium manganese iron phosphate material is provided, comprising the following steps:

[0033] S1, grinding the iron source, the phosphorus source, the manganese source and the first carbon source for the first time to obtain a carbon-coated manganese iron phosphate solid solution;

[0034] S2, spray drying and first sintering the carbon-coated ferromanganese phosphate solid solution in sequence to obtain a sintered material;

[0035] S3, performing a second grinding on the sintered material, the lithium source and the second carbon source to obtain a grinding material;

[0036] S4. The ground material is spray-dried, second-sintered and crushed in sequence to obtain lithium manganese iron phosphate material.

[0037] The preparation method of the lithium manganese iron phosphate material of the present invention comprises grinding an iron source, a phosphorus source, a manganese source and a first carbon source once to obtain a carbon-coated manganese iron phosphate solid solution to form a crystal nucleus; then the solid solution is spray-dried and sintered once. During the sintering process, the crystal nucleus can grow particles under the coating of the first carbon source, thereby facilitating the improvement of the compaction density of the material.

[0038] When the sintering material, lithium source and second carbon source are ground for the second time, lithium is supplemented and the second carbon source is added. During the sintering process, lithium is embedded in the ferromanganese phosphate lattice, and the particles can be prevented from growing excessively under the coating of the second carbon source, which can improve the electronic conductivity of lithium manganese iron phosphate (LMFP) and enhance its ionic conductivity.

[0039] The present invention adopts a two-stage sintering method. The first sintering is beneficial to the crystallization nucleation of particles, and the second sintering is beneficial to the further growth of particles. It not only improves the integrity of the material's crystal structure, but also can effectively control the particle size of the final product and shorten the ion transmission path, thereby facilitating the improvement of the material's compaction density and electrochemical performance.

[0040] The preparation method of the present invention can also flexibly adjust the compaction performance and conductivity of the lithium manganese iron phosphate material by adjusting the coating amount of the second carbon source, so that it can better meet the needs of different application scenarios.

[0041] The present invention adopts a high-temperature solid phase method to prepare the lithium iron manganese phosphate material. The preparation method has a simple process, is easy to operate, does not require a complicated process flow and high production cost, and is conducive to the large-scale industrial application of the lithium iron manganese phosphate material.

[0042] In some embodiments of the present invention, in step S1, the iron source includes one or more of ferric phosphate dihydrate, ferric phosphate (anhydrous ferric phosphate), ferric chloride, ferric sulfate, ferric nitrate and ferrous sulfate heptahydrate.

[0043] In some embodiments of the present invention, in step S1, the iron source includes dihydrated iron phosphate. In the preparation process of the iron phosphate material, the flash drying and roasting sections mainly use high temperature to remove free water and crystal water to obtain anhydrous iron phosphate. The synthesis of the iron phosphate material has been completed before flash evaporation, and the dihydrated iron phosphate is in an amorphous state. Therefore, it is feasible to synthesize the lithium iron manganese phosphate material using the dihydrated iron phosphate before flash evaporation in the present invention, and the production cost is greatly reduced.

[0044] In some embodiments of the present invention, in step S1, the phosphorus source includes one or more of phosphoric acid, diammonium hydrogen phosphate, lithium monohydrogen phosphate, lithium dihydrogen phosphate and lithium phosphate.

[0045] In some embodiments of the present invention, in step S1, the manganese source includes one or more of manganese sulfate, manganese acetate, manganese oxalate, manganese phosphate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide.

[0046] In some embodiments of the present invention, in step S1, the first carbon source includes one or more of Super P, graphene, carbon nanotubes and acetylene black; the first carbon source is an inorganic carbon source, and the coating of the inorganic carbon source is beneficial to the formation of crystal nuclei of the manganese iron phosphate solid solution, which helps to form a complete lithium manganese iron phosphate crystal form during the low-temperature sintering process and is beneficial to grain growth.

[0047] In some embodiments of the present invention, in step S1, in the carbon-coated ferromanganese phosphate solid solution, the molar ratio of Fe element, Mn element and P element is (0.4-0.6): (0.4-0.6):1.

[0048] In some embodiments of the present invention, in step S1, the molar ratio of C element to P element in the carbon-coated ferromanganese phosphate solid solution is (0.01-0.3):1; typically but not limitatively, for example, in step S1, the molar ratio of C element to P element in the carbon-coated ferromanganese phosphate solid solution can be 0.01:1, 0.025:1, 0.05:1, 0.075:1, 0.080:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1 or a range of any two thereof.

[0049] In some embodiments of the present invention, in step S1, the first grinding includes: grinding until the average particle size of the solid particles is 0.35-2 μm.

[0050] In some embodiments of the present invention, in step S1, the first grinding includes wet grinding, preferably sand grinding.

[0051] In some embodiments of the present invention, in step S2, the first sintering includes: heat preservation treatment at 300-600°C for 2-7h; typically but not limitatively, for example, the temperature of the first sintering can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or a range consisting of any two thereof; the time of the first sintering can be 2h, 3h, 4h, 5h, 6h, 7h or a range consisting of any two thereof.

[0052] The present invention performs low-temperature primary sintering at 300-600° C., and the crystal nuclei can be coated by the first carbon source, such as Super P, to make the particles grow, which is beneficial to improving the compaction density of the material.

[0053] In some embodiments of the present invention, in step S2, the first sintering is performed under a nitrogen atmosphere.

[0054] In some embodiments of the present invention, in step S3, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium chloride, lithium dihydrogen phosphate and lithium acetate.

[0055] In some embodiments of the present invention, in step S3, the second carbon source includes one or more of glucose, sucrose, starch, polyethylene glycol, oxalic acid and citric acid; and the second carbon source is an organic carbon source.

[0056] In some embodiments of the present invention, in step S3, the molar ratio of the Li element in the lithium source to the Fe element in the sintering material is 1:(0.4-0.6).

[0057] In some embodiments of the present invention, in step S3, the molar ratio of the C element in the second carbon source to the Li element in the lithium source is (0.01-0.3):1; typically but not limitatively, for example, the molar ratio of the C element in the second carbon source to the Li element in the lithium source can be 0.01:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1 or a range of any two thereof.

[0058] In some embodiments of the present invention, in step S3, the second grinding includes: grinding until the average particle size of the solid particles is 0.35-0.45 μm.

[0059] In some embodiments of the present invention, in step S3, the second grinding includes wet grinding, preferably sand grinding.

[0060] In some embodiments of the present invention, in step S4, the second sintering includes: heat preservation treatment at 600-780°C for 5-9h; typically but not limitatively, for example, the temperature of the second sintering can be 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C or a range consisting of any two thereof; the time of the second sintering can be 5h, 6h, 7h, 8h, 9h or a range consisting of any two thereof.

[0061] The invention performs high-temperature secondary sintering at 600-780° C., lithium is embedded in the ferromanganese phosphate lattice, and the particles can be prevented from excessively growing under the coating of the organic carbon source, thereby simultaneously improving the electronic conductivity and ionic conductivity of the material.

[0062] In some embodiments of the present invention, in step S4, the second sintering is performed under a nitrogen atmosphere.

[0063] Example 1

[0064] The method for preparing the lithium iron manganese phosphate material provided in this embodiment comprises the following steps:

[0065] S1. Add ferric phosphate dihydrate, phosphoric acid, manganese tetraoxide and Super P into pure water for sand grinding for 50 minutes until the average particle size D50 of the solid particles is 0.8 μm, thereby obtaining a carbon-coated manganese ferrophosphate solid solution; wherein, in the carbon-coated manganese ferrophosphate solid solution, the molar ratio of Fe element, Mn element and P element is 0.5:0.5:1, and the molar ratio of C element to P element is 0.045:1;

[0066] S2, spray drying the carbon-coated ferromanganese phosphate solid solution, and heat-treating it at 400° C. for 5 h in a nitrogen atmosphere to obtain a sintered material;

[0067] S3, sand-grinding the sintering material, lithium carbonate, sucrose and pure water, wherein the molar ratio of the Fe element in the sintering material to the Li element in the lithium source is 0.5:1, and the molar ratio of the C element in the sucrose to the Li element in the lithium carbonate is 0.015:1, and sand-grinding for 50 minutes until the average particle size D50 of the solid particles is 0.4 μm, to obtain a grinding material;

[0068] S4. The above-mentioned ground material is spray-dried, heat-treated at 750° C. for 7 hours under a nitrogen atmosphere, and crushed to obtain lithium manganese iron phosphate material.

[0069] Example 2

[0070] The method for preparing the lithium iron manganese phosphate material provided in this embodiment comprises the following steps:

[0071] S1. Add anhydrous ferric phosphate, phosphoric acid, manganese dioxide and acetylene black into pure water for sand grinding for 65 minutes until the average particle size D50 of the solid particles is 0.75 μm, thereby obtaining a carbon-coated ferromanganese phosphate solid solution; wherein, in the carbon-coated ferromanganese phosphate solid solution, the molar ratio of Fe element, Mn element and P element is 0.4:0.6:1, and the molar ratio of C element to P element is 0.05:1;

[0072] S2, spray drying the carbon-coated ferromanganese phosphate solid solution, and heat-treating it at 400° C. for 5 h in a nitrogen atmosphere to obtain a sintered material;

[0073] S3, sand-milling a sintering material, lithium carbonate, glucose and pure water, wherein the molar ratio of the Fe element in the sintering material to the Li element in the lithium source is 0.4:1, and the molar ratio of the C element in the glucose to the Li element in the lithium carbonate is 0.015:1, and sand-milling for 65 minutes until the average particle size D50 of the solid particles is 0.41 μm, to obtain a grinding material;

[0074] S4. The above-mentioned ground material is spray-dried, and heat-treated at 730° C. for 6 hours under a nitrogen atmosphere, and then crushed to obtain lithium manganese iron phosphate material.

[0075] Example 3

[0076] The method for preparing the lithium iron manganese phosphate material provided in this embodiment comprises the following steps:

[0077] S1. Adding ferric phosphate dihydrate, lithium dihydrogen phosphate, manganese tetraoxide and Super P into pure water for sand grinding for 65 minutes until the average particle size D50 of the solid particles is 0.84 μm, to obtain a carbon-coated manganese ferrophosphate solid solution; wherein, in the carbon-coated manganese ferrophosphate solid solution, the molar ratio of Fe element, Mn element and P element is 0.6:0.4:1, and the molar ratio of C element to P element is 0.045:1;

[0078] S2, spray drying the carbon-coated ferromanganese phosphate solid solution, and heat-treating it at 350° C. for 6 hours under a nitrogen atmosphere to obtain a sintered material;

[0079] S3, sand-grinding a sintering material, lithium carbonate, sucrose and pure water, wherein the molar ratio of the Fe element in the sintering material to the Li element in the lithium source is 0.6:1, and the molar ratio of the C element in the sucrose to the Li element in the lithium carbonate is 0.02:1, and sand-grinding for 45 minutes until the average particle size D50 of the solid particles is 0.42 μm, to obtain a grinding material;

[0080] S4. The above-mentioned ground material is spray-dried, heat-treated at 770° C. for 5 hours under a nitrogen atmosphere, and crushed to obtain lithium manganese iron phosphate material.

[0081] Comparative Example 1

[0082] The preparation method of the lithium iron manganese phosphate material provided in this comparative example refers to Example 1, with the only difference being that in step S1, Super P is not added to obtain a solid solution of manganese iron phosphate; and in step S3, the molar ratio of the C element in sucrose to the Li element in lithium carbonate is 0.05:1.

[0083] Comparative Example 2

[0084] The preparation method of the lithium manganese iron phosphate material provided in this embodiment refers to Example 1, except that step S2 is not performed; the carbon-coated manganese iron phosphate solid solution, lithium carbonate, sucrose and pure water are directly mixed and sand-milled.

[0085] Test example

[0086] The compacted density and specific surface area (BET) of the lithium manganese iron phosphate materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the results are shown in Table 1.

[0087] Compaction density test method: using a compaction density meter for testing;

[0088] Specific surface area test method: Use specific surface area meter for detection.

[0089] Table 1

[0090] <![CDATA[Compaction density (g / cm 3 )]]> <![CDATA[Specific surface area (m 2 / g) <!-- 5 -->]]> Example 1 2.31 23.25 Example 2 2.28 24.29 Example 3 2.29 23.11 Comparative Example 1 2.17 28.16 Comparative Example 2 2.15 30.94

[0091] The electrochemical properties of the lithium manganese iron phosphate materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the results are shown in Table 2.

[0092] Test method: PVDF, Super P, N-methylpyrrolidone and lithium manganese iron phosphate material are homogenized, wherein the mass ratio of lithium manganese iron phosphate material, PVDF and Super P is 94:3:3. Then the circular pole piece is obtained by coating, drying and punching, and finally the circular pole piece, diaphragm and lithium sheet are assembled into a button cell in the glove box for testing. The button cell is charged and discharged in the voltage range of 2.0 to 4.3V.

[0093] Table 2

[0094]

[0095]

[0096] It can be seen from Table 1 and Table 2 that the lithium manganese iron phosphate material prepared by the method for preparing the lithium manganese iron phosphate material of the present invention has improved physical properties and electrical properties, and has excellent compaction density and electrochemical properties.

[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing lithium manganese iron phosphate material, characterized in that: The steps include: S1, grinding the iron source, the phosphorus source, the manganese source and the first carbon source for the first time to obtain a carbon-coated manganese iron phosphate solid solution; S2, spray drying and first sintering the carbon-coated ferromanganese phosphate solid solution in sequence to obtain a sintered material; S3, performing a second grinding on the sintered material, the lithium source and the second carbon source to obtain a grinding material; S4, spray drying, second sintering and crushing the ground material in sequence to obtain the lithium manganese iron phosphate material.

2. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In step S1, at least one of the following features (1) to (4) is included; (1) The iron source includes one or more of ferric phosphate dihydrate, ferric phosphate, ferric chloride, ferric sulfate, ferric nitrate and ferrous sulfate heptahydrate; (2) the phosphorus source comprises one or more of phosphoric acid, diammonium hydrogen phosphate, lithium monohydrogen phosphate, lithium dihydrogen phosphate and lithium phosphate; (3) The manganese source includes one or more of manganese sulfate, manganese acetate, manganese oxalate, manganese phosphate, manganese pyrophosphate, manganese dioxide and manganese tetraoxide; (4) The first carbon source includes one or more of Super P, graphene, carbon nanotubes and acetylene black.

3. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In step S1, in the carbon-coated ferromanganese phosphate solid solution, the molar ratio of Fe element, Mn element and P element is (0.4-0.6): (0.4-0.6):

1.

4. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In step S1, in the carbon-coated ferromanganese phosphate solid solution, the molar ratio of the C element to the P element is (0.01-0.3):

1.

5. The method for preparing lithium iron manganese phosphate material according to claim 4, characterized in that: In step S1, the first grinding includes: grinding until the average particle size of the solid particles is 0.35-2 μm.

6. The method for preparing lithium iron manganese phosphate material according to claim 4, characterized in that: In step S2, the first sintering includes: heat preservation treatment at 300-600°C for 2-7h.

7. The method for preparing lithium iron manganese phosphate material according to claim 6, characterized in that: In step S3, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium chloride, lithium dihydrogen phosphate and lithium acetate; And / or, the second carbon source includes one or more of glucose, sucrose, starch, polyethylene glycol, oxalic acid and citric acid.

8. The method for preparing lithium iron manganese phosphate material according to claim 6, characterized in that: In step S3, the molar ratio of the Li element in the lithium source to the Fe element in the sintering material is 1:(0.4-0.6); And / or, the molar ratio of the C element in the second carbon source to the Li element in the lithium source is (0.01-0.3):

1.

9. The method for preparing lithium iron manganese phosphate material according to claim 7, characterized in that: In step S3, the second grinding includes: grinding until the average particle size of the solid particles is 0.35-0.45 μm.

10. The method for preparing lithium iron manganese phosphate material according to claim 8, characterized in that: In step S4, the second sintering includes: heat preservation treatment at 600-780° C. for 5-9 hours.